2020
DOI: 10.3390/app10061911
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a Dielectric Barrier Discharge Plasma Actuator to Control Turbulent Boundary Layer Separation

Abstract: A numerical investigation was carried out to explore the effects of a dielectric barrier discharge (DBD) plasma actuator on a three-dimensional incompressible, separated flow. The test article selected for the simulations was the National Aeronautical and Space Administration (NASA) wall-mounted hump model. The simulations were run at a Reynolds number of 936,000, based on hump chord length, and a freestream Mach number of 0.1. Hybrid partially averaged Navier–Stokes/large-eddy simulations (PANS/LES) were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Once away from the wall or further downstream, velocity fluctuations decrease rapidly due to the viscosity effect. Therefore, many studies on macro flow control actually ignore the impact of the cyclical change [45][46][47]. In addition, it should be reasonable that consider that such a small local induced flow velocity fluctuation has limited influence on the large-scale flow control with large free-stream velocity (such as tens of meters per second), especially for flow around the non-stall airfoil that is the focus of this paper.…”
Section: Dbd Plasma Actuator Model 21 Single Dbd Plasma Actuator Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Once away from the wall or further downstream, velocity fluctuations decrease rapidly due to the viscosity effect. Therefore, many studies on macro flow control actually ignore the impact of the cyclical change [45][46][47]. In addition, it should be reasonable that consider that such a small local induced flow velocity fluctuation has limited influence on the large-scale flow control with large free-stream velocity (such as tens of meters per second), especially for flow around the non-stall airfoil that is the focus of this paper.…”
Section: Dbd Plasma Actuator Model 21 Single Dbd Plasma Actuator Modelmentioning
confidence: 99%
“…Many studies have confirmed that the most effective position of separation control is near the natural separation point, and the actuator in the deep separation zone will almost completely fail [37,47,56]. Moreover, the natural separation point moves upstream with the angle of attack, which means that a single actuator cannot always be in the best position.…”
Section: Joint Simulation Of Ps and Ssd Actuatorsmentioning
confidence: 99%
“…Some studies were performed on the possibility of controlling the flow by an off-body energy addition [19,20]. Alternatively, several research efforts have been devoted to the development of plasma actuators in which the air close to the wall is locally ionized by an electrical discharge [21][22][23][24][25][26][27]. This technology was also investigated for controlling flow separation in rocket nozzles for space launchers [28].…”
Section: Introductionmentioning
confidence: 99%